Efektivitas Penggunaan Teknologi AI Dalam Pembelajaran Bahasa Inggris - Dhanan Abimanto; Iwan Mahendro (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This research aims to explore the effectiveness of using artificial intelligence (AI) in English language learning. The research method used is mixed-methods, combining quantitative and qualitative approaches. The research participants consist of 100 students of UNIMAR AMNI who utilize AI as a language learning method. The results of the study show a significant improvement in listening, speaking, reading, and writing skills after using AI. These findings support the effectiveness of AI utilization in language learning. Furthermore, this research fills the research gap in the context of AI usage in English language learning in educational institutions. The practical implication of this research is the need for integrating AI into language learning curricula to enhance effective and efficient learning outcomes. This study provides a significant contribution to our understanding of AI implementation in language learning and highlights the immense potential of AI in developing innovative and adaptive teaching methods.